2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin promotes injury‐induced vascular neointima formation in mice. Issue 9 (19th June 2019) - Guo, Shumin; Zhang, Rui; Liu, Qian; Wan, Qiangyou; Wang, Yuanyang; Yu, Yu; Liu, Guizhu; Shen, Yujun; Yu, Ying; Zhang, Jian
ABSTRACT: 2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin (TCDD) is an environmental pollutant that causes cardiovascular toxicity. The phenotypic transformation of vascular smooth muscle cells (VSMCs) from the contractile to the synthetic phenotype is a hallmark of vascular response to injury. However, the precise role and molecular mechanism of TCDD in vascular remodeling remains unknown. In the present study, we found that TCDD treatment promoted VSMC phenotypic transition from contractile to synthetic phenotype and exaggerated vascular neointimal hyperplasia after wire injury in mice. TCDD treatment enhanced VSMC entry into cell cycle from G0/G1 phase to S and G2/M phase. The expression of cyclin D1, cyclin‐dependent kinase 4 (CDK4), and its phosphorylation were coordinately increased in response to TCDD treatment. Knocking down of aryl hydrocarbon receptor (AHR) inhibited VSMC phenotypic transition induced by TCDD and promoted S/G2 phase cell cycle arrest. TCDD treatment markedly increased oncogenic c‐Jun gene expression in VSMCs. ChIP assay revealed the direct binding of AHR on the promoter of c‐Jun to up‐regulate the mRNA expression of c‐Jun. Silencing of c‐Jun gene enhanced the expression of p53 and p21, whereas attenuated the expression of CDK4 and cyclin D1 leading to the decrease in the TCDD‐stimulated VSMC proliferation and synthetic phenotype transition in vitro. In vivo study showed that genetic ablation of c‐Jun in VSMCs restricted injury‐induced neointimal hyperplasia in TCDD‐treated mice. Thus, TCDD exposure exaggerated injury‐induced vascular remodeling by the activation of AHR and up‐regulation of the expression of its target gene c‐Jun, indicating that inhibition of AHR may be a promising prevention strategy for TCDD‐associated cardiovascular diseases.—Guo, S., Zhang, R., Liu, Q., Wan, Q., Wang, Y., Yu, Y., Liu, G., Shen, Y., Yu, Y., Zhang, J. 2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin promotes injury‐induced vascular neointima formation in mice. FASEB J. 33, 10207–10217 (2019). www.fasebj.org